2018
DOI: 10.1093/gigascience/giy146
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequence of the oriental lung fluke Paragonimus westermani

Abstract: BackgroundFoodborne infections caused by lung flukes of the genus Paragonimus are a significant and widespread public health problem in tropical areas. Approximately 50 Paragonimus species have been reported to infect animals and humans, but Paragonimus westermani is responsible for the bulk of human disease. Despite their medical and economic importance, no genome sequence for any Paragonimus species is available.ResultsWe sequenced and assembled the genome of P. westermani, which is among the largest of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 52 publications
3
48
1
Order By: Relevance
“…Nevertheless, in a larger phylogenetic context, the gene repertoire seems to have experienced a reduction in acanthocephalan evolution. Thus, we detected only 73% of the expected metazoan genes in the P. laevis transcriptome, a dimension that was reported also for parasitic helminths [161,162]. The reduction in gene repertoire was also reflected in a reduced complement of proteins regulating development, as expected for a parasite with comparably simple body organization [159].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Nevertheless, in a larger phylogenetic context, the gene repertoire seems to have experienced a reduction in acanthocephalan evolution. Thus, we detected only 73% of the expected metazoan genes in the P. laevis transcriptome, a dimension that was reported also for parasitic helminths [161,162]. The reduction in gene repertoire was also reflected in a reduced complement of proteins regulating development, as expected for a parasite with comparably simple body organization [159].…”
Section: Discussionsupporting
confidence: 50%
“…The reduced number of usually conserved metazoan genes presumably reflects gene loss on the lineage to P. laevis, as it is common in parasite evolution [63,[158][159][160]. This is indeed very likely considering that almost identical percentages of metazoan genes (74% to 77%) were detected by BUSCO in the genome assemblies of four parasitic trematodes [161]. Although these counts refer to the subset of usually conserved metazoan genes, the relation could apply to the entire gene repertoire, as illustrated again by other taxa.…”
Section: Metazoan Genes In Acanthocephalan Evolutionmentioning
confidence: 99%
“…Similar regions in other studies of mt genomes have also been shown as problematic [46,47]. Therefore, the PacBio single-molecule real-time sequencing method has been used by researchers in recent studies to characterize long and difficult to sequence repetitive regions of flatworm mitogenomes [48,49]. Nonetheless, the coding regions of the mt genomes of Brachylecithum sp.…”
Section: Gene Organization Size and Nucleotide Content Of Mitogenomesmentioning
confidence: 81%
“…All 12 protein-encoding genes, 22 tRNAs and two rRNAs had high sequence similarities (> 99.2%) to those in published mitochondrial genomes and occurred in the same order. However, there is clear evidence [17,18,38] that conventional sequencing methods are not suited to the sequencing of long non-coding regions in mitochondrial genomes. This obstacle has been overcome through the use of nanopore-sequencing, which bodes well for future mitochondrial genome investigations.…”
Section: Overcoming the Challenges Of Sequencing The Tandem-repetitivmentioning
confidence: 99%